PENERAPAN METODE EKSPERIMEN UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 65 PEKANBARU - Desi Purnamasari; Mahmud Alpusari; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstrack.The purpose of this research is to improve the achievement of fifth grade students of SDN 65 Pekanbaru in science field, year 2012/2013 through “the application of experimental method”. This research was conducted from April 2013 until Mei 2013. Subject of this research is fifth grade students of SDN 65 Pekanbaru. They are 19 pupils. 10 male and 9 female. This is a collaborative action research (teacher and the researcher), contains of 2 cycles. First cycle contains 2 meetings and second cycle contains 2 meetings. Research’s parameter covers students’ achievement after action conducted in every cycle (daily test I and daily test II), observation sheet/ students’ activity observation. Data was analyzed descriptively. Data shows that students’ achievement improves. Before experiment, only 4 pupils (21,05%) got daily test result above or same with school’s standard Kriteria Ketuntasan Minimal (KKM), which is 70. While 15 pupils (78,94) are still under school standard KKM. After experiment in first cycle, 73,68% pupils got daily test result above or same with KKM. And second cycle, the number become 89,4%. Students’ activities in learning process (cycle I and II) are categorized good, with the average number 89,4%, while teacher’s activities are categorized good, with average number 92,5%. So, we can say that hypothesis in this research “the application of experimental method in IPA learning can improve the achievement of fifth grade students of SDN 65 Pekanbaru in science field” can be accepted. Keyword: Experiment Method, Result of Learning Student